2023
DOI: 10.1186/s12913-023-09817-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patient perceived values during outpatient encounters: an empirical study from Chinese public hospitals

Abstract: Background Focusing on patients’ perceived values is essential for patient-centered health care. Only by identifying the patient’s preferred values can we better meet their needs and provide them with valuable medical services. This study aimed to construct and validate a research model to obtain an overall quantification of patient value during outpatient encounters. Methods The development of the research model was based on the reviewed literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Differences in perceptions between health-care subsidy and non-subsidy customers are noted. Health-care subsidies play an important factor in assessing the goal of voucher schemes (health-care prevention and chronic disease management), service quality and effectiveness of DHCs (Chen, 2023; Johnson et al , 2012; Liu et al , 2023; Yam et al , 2019). Furthermore, core services have a negative impact on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in perceptions between health-care subsidy and non-subsidy customers are noted. Health-care subsidies play an important factor in assessing the goal of voucher schemes (health-care prevention and chronic disease management), service quality and effectiveness of DHCs (Chen, 2023; Johnson et al , 2012; Liu et al , 2023; Yam et al , 2019). Furthermore, core services have a negative impact on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Subsidy is important because it increases the use of outpatient care in terms of the number of patients, visitation and monthly spending (Kang et al , 2022). Liu et al (2023) showed that the price of medical services affects patient perceptions. Chen and Miraldo (2022) found a decrease in transparency of hospitality quality on the price of health-care procedures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations